The genomic and functional landscapes of developmental plasticity in the American cockroach - Sheng Li (Nature Portfolio, 2018)
The American cockroach (Periplaneta americana) is an hemimetabolous insect with rapid growth, high fecundity, and remarkable tissue-regeneration capability. Here Li et al sequence its 3.38-Gb genome and perform the functional studies, yielding insights into its environmental adaptation and developmental plasticity.